Prawitagarden.Com Website As A Promotional Media For Honey Derivative Products From The Forest Farmers Group: Website Prawitagarden.Com Sebagai Media Promosi Produk Turunan Madu Kelompok Petani Hutan - Muhammad Lulu Latif Usman; Ratih Windu Arini; Muhamad Azrino Gustalika (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Damakradenan Village, Ajibarang District has great potential in pure honey production through the “Petani Muda Prawita” Forest Farmer Group. This group produces various types of honey, including klanceng honey, mellifera bee honey, Apis cerana honeycomb honey, and sachet honey, with the main target market being children. However, product sales are still limited in the Banyumas Regency area and digital marketing has not been running optimally because it only relies on Instagram social media without an official website. This problem has an impact on limited market reach and consumer trust levels. This community service program is implemented to help partners increase promotion and sales through website development as a digital marketing medium. The stages of the activity include creating a website using the WordPress framework, the indexation process so that it can be found on the Google search engine, and website management training for partners. The results of the activity show that partners now have an official website with the domain prawitagarden.com, indexed on the Google search engine, and partners have been equipped with independent website administration skills. The existence of the website is expected to expand market reach, increase consumer trust, and support the continuity of the Prawita Garden honey business digitally